PENGARUH BAURAN PEMASARAN DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN MOBIL SUZUKI SX4 S-CROSS PADA PT. SEJAHTERA BUANA TRADA SUZUKI MOBIL PEKANBARU - Haris Tri Elang Sakti; Meyzi Heriyanto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This research was conducted at PT. Sejahtera Buana Trada Suzuki Mobil Pekanbaru, located on SM Amin Street, Simpang Baru, Tampan, Pekanbaru, Riau. The purpose of this study was to determine the effect of marketing mix and service quality on buying desicion of Suzuki SX4 S-Cross Car at PT. Sejahtera Buana Trada Suzuki Mobil Pekanbaru partially and simultaneously. In this research the method used is quantitative descriptive analysis with SPSS program. The population in this study are allconsumers who purchase the SX4 S-Cross Car at PT. Sejahtera Buana Trada Suzuki Mobil Pekanbaru in the last year of 2019 totaling 95 people. Where the samples in this study are consumers of PT. Sejahtera Buana Trada Suzuki Mobil Pekanbaru as many as 95 respondents. To determine the sample using the Census Method. Data collection techniques through questionnaires and interviews, types and sources of data using primary data and secondary data, measurement collection techniques using a Likert scale.From the analysis of data which includes validity, reliability, simple linear regression analysis, multiple linear analysis, determination analysis and significance test with t test (partial test), and f test (simultaneous). The results of this study indicate that the results of the first t test hypothesis testing, marketing mix on buying desicion is t arithmetic (9.246)> t table (1,6614) means that marketing mix has a significant effect on buying desicion. Second, the service quality on buying desicion is t arithmetic (11.278)> t table (1.6615) means that the service quality significantly influences buying desicion. The f test results of marketing mix and service quality have a significant effect on buying desicion, namely f arithmetic (80.317)> F_ table (3.10). This means that marketing mix and service quality simultaneously have a significant effect on buying desicion at PT. Sejahtera Buana Trada Suzuki Mobil Pekanbaru. Keywords: Marketing Mix, Service Quality, Buying Decision